A Comparative Study of Microwave-Assisted and Conventional Heating Approaches for the Multicomponent Synthesis of 4,6-Diarylpyrimidines - Christian A. Becerra-Rivas; Paola Andrea Cuervo Prado; Fabian Orozco-Lopez (Universitas Scientiarum)
A series of 2-amino-4,6-diarylpyrimidines were synthesized using a Biginelli-type three-component strategy optimized in conventional-heated reflux, in contrast to a non-conventional approach using a mono-mode microwave reactor. Conventional heating protocols involved organic solvents and general base catalysis, whereas a microwave-assisted method followed experimental protocols framed within the principles of green chemistry by using CaCl2 as a catalyst in solvent-free conditions. This study revealed that although conventional heating led to the main product in higher yields at longer reaction times, the microwave strategy suceeded in substantially shorter reaction times, with yields ranging from acceptable to good and efficiencies comparable to conventional heating methodology.